2015
DOI: 10.1063/1.4935703
|View full text |Cite
|
Sign up to set email alerts
|

A minimal coupled fluid-discrete element model for bedload transport

Abstract: Shields number, and that the influence of the granular parameters on the macroscopic results are weak. Nevertheless, the analysis of the corresponding depth profiles reveals an evolution of the depth structure of the granular phase with varying restitution and friction coefficients, which denotes the non-trivial underlying physical mechanisms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(97 citation statements)
references
References 54 publications
(72 reference statements)
7
89
0
1
Order By: Relevance
“…Before they came to a halt, these particles destabilized other particles resting on the bed interface, and thereby they initiated low sediment transport. Our findings are in line with recent simulations based on discrete element methods. Maurin et al [] obtained a similar particle velocity profile to the one reported in Figure a. Clark et al [] showed how important the particle Stokes number is when studying particle dynamics at the onset of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Before they came to a halt, these particles destabilized other particles resting on the bed interface, and thereby they initiated low sediment transport. Our findings are in line with recent simulations based on discrete element methods. Maurin et al [] obtained a similar particle velocity profile to the one reported in Figure a. Clark et al [] showed how important the particle Stokes number is when studying particle dynamics at the onset of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Elle fait intervenir les forces de portance, de flottabilité et de traînée. La force de traînée a été modifiée par rapport au travail initié par MAURIN et al (2015) pour prendre en compte des nombres de Reynolds de particule plus élevés. Les modifications étant validées, les premières simulations pour le Nord Cotentin ont été réalisées afin de les appliquer in-fine aux sites EMR hydrolien.…”
Section: Discussionunclassified
“…The model has been validated with turbulent bedload transport experiments, in terms of both the sediment transport rate and granular depth profiles. More details can be found in [7,11]. This model has also been used to analyse the dense granular rheology in turbulent bedload transport [12].…”
Section: Coupled Fluid-discrete Element Modelmentioning
confidence: 99%
“…The friction coefficient is set to 0.4, and a restitution coefficient of 0.5 is taken consistently with the experimental validation [7].…”
Section: Coupled Fluid-discrete Element Modelmentioning
confidence: 99%
See 1 more Smart Citation